Polityka wynagradzania jako czynnik efektywności zarządzania - Bratnicki, Mariusz; Majowska, Magdalena (Reward policies as a factor of management effectiveness, 2005)
In the present article, the authors made an attempt to improve the general understanding of compensation issues. A full understanding of decision making as far as reward has been highlighted and explained through the examination of the reward policies considered in the light of management effectiveness. The authors focused on the role of the compensation policies in achieving strategic goals set by an organization. Some guidelines of how to create an effective reward system were provided.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1092, s. 535-541